2017
DOI: 10.1038/bjc.2017.277
|View full text |Cite
|
Sign up to set email alerts
|

RNAi screen reveals synthetic lethality between cyclin G-associated kinase and FBXW7 by inducing aberrant mitoses

Abstract: Background:F-box and WD40 repeat domain-containing 7 (FBXW7) is an E3 ubiquitin ligase involved in the ubiquitination and degradation of multiple oncogenic substrates. The tumour suppressor function is frequently lost in multiple cancers through genetic deletion and mutations in a broad range of tumours. Loss of FBXW7 functionality results in the stabilisation of multiple major oncoproteins, culminating in increased cellular proliferation and pro-survival pathways, cell cycle deregulation, chromosomal instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Therefore, the stability of the c-MYC protein is strictly controlled by FBXW7, which is an E3 ubiquitin ligase involved in ubiquitination and degradation of various carcinogenic substrates that contain F-box and WD40 repeat domains. 24 Many studies have shown that abnormal expression of FBXW7 is the main cause of tumorigenesis. 25 27 Inactivation of FBXW7 expression will enhance the proliferation and migration of tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the stability of the c-MYC protein is strictly controlled by FBXW7, which is an E3 ubiquitin ligase involved in ubiquitination and degradation of various carcinogenic substrates that contain F-box and WD40 repeat domains. 24 Many studies have shown that abnormal expression of FBXW7 is the main cause of tumorigenesis. 25 27 Inactivation of FBXW7 expression will enhance the proliferation and migration of tumours.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that siRNA‐mediated GAK knockdown results in mitotic arrest during metaphase and multipolar spindle formation . Due to this mitotic involvement, GAK is a potential drug target for the treatment of BXW7‐deficient tumors, such as cholangiocarcinoma . GAK was also identified as a potential target for the inhibition of prostate cancer growth in cells expressing androgen receptor splice variants .…”
Section: Introductionmentioning
confidence: 99%
“…To date all studies of the role of GAK in prostate cancer have utilized knock-down of the whole protein. 28 We now show for the first time that inhibition of the GAK kinase domain alone can block the growth of prostate cancer cells. Our results demonstrate that the kinase and not the auxilin-homology domain is critical for this phenotype in cells.…”
Section: Discussionmentioning
confidence: 76%